Understanding Client Support Strategies to Improve Clinical Outcomes in an Online Mental Health Intervention - Chikersal, Prerna; Belgrave, Danielle; Doherty, Gavin; Enrique, Angel; Palacios, Jorge E.; Richards, Derek; Thieme, Anja (CHI 2020, 2020)
Online mental health interventions are increasingly important in providing access to, and supporting the effectiveness of, mental health treatment. While these technologies are effective, user attrition and early disengagement are key challenges. Evidence suggests that integrating a human supporter into such services mitigates these challenges, however, it remains under-studied how supporter involvement benefits client outcomes, and how to maximize such effects. We present our analysis of 234,735 supporter messages to discover how different support strategies correlate with clinical outcomes. We describe our machine learning methods for: (i) clustering supporters based on client outcomes; (ii) extracting and analyzing linguistic features from supporter messages; and (iii) identifying context-specific patterns of support. Our findings indicate that concrete, positive and supportive feedback from supporters that reference social behaviors are strongly associated with better outcomes; and show how their importance varies dependent on different client situations. We discuss design implications for personalized support and supporter interfaces.
http://dx.doi.org/10.1145/3313831.3376341